2006
DOI: 10.1029/2005jb003806
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal filtering using principal component analysis and Karhunen‐Loeve expansion approaches for regional GPS network analysis

Abstract: [1] Spatial filtering is an effective way to improve the precision of coordinate time series for regional GPS networks by reducing so-called common mode errors, thereby providing better resolution for detecting weak or transient deformation signals. The commonly used approach to regional filtering assumes that the common mode error is spatially uniform, which is a good approximation for networks of hundreds of kilometers extent, but breaks down as the spatial extent increases. A more rigorous approach should r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
347
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(378 citation statements)
references
References 59 publications
10
347
0
Order By: Relevance
“…The GPS time series thus calculated contain significant CMEs, which are considered to be caused by unmodeled, or mismodeled, motions of satellite orbits, reference frame, or earth orientation parameters (Dong et al, 2006). The CMEs were removed prior to the EOF analysis to avoid any leakage of coseismic/postseismic signals into the modes representing CMEs.…”
Section: Gps Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The GPS time series thus calculated contain significant CMEs, which are considered to be caused by unmodeled, or mismodeled, motions of satellite orbits, reference frame, or earth orientation parameters (Dong et al, 2006). The CMEs were removed prior to the EOF analysis to avoid any leakage of coseismic/postseismic signals into the modes representing CMEs.…”
Section: Gps Analysismentioning
confidence: 99%
“…They subsequently used it to extract the interseismic vertical deformation field of the Japanese islands. Dong et al (2006) used EOF analysis to identify/remove the modes corresponding to common mode errors (CMEs) that are often associated with the GPS time series. In the case of the 2011 Tohoku-oki earthquake, Chang and Chao (2011) applied EOF analysis to the GPS kinematic time series obtained from GEONET and identified several modes corresponding to the coseismic, and postseismic, deformations.…”
Section: Introductionmentioning
confidence: 99%
“…This empirical method, equivalent to a three-parameter Helmert transformation (Dong et al 2006), was shown (see Table 3) to significantly reduce the amplitudes of the flicker and white noise in the time series (Williams et al 2004). A more rigorous approach to the problem using principal component analysis and Karhunen-Loeve expansion was performed by Dong et al (2006) who found that the results were similar to the stacking method because the sites were spatially correlated over large wavelengths. Other groups have also applied empirical orthogonal functions to the problem with similar results (Johansson et al 2002).…”
Section: Noise Characteristics Of Site Coordinate Time Seriesmentioning
confidence: 99%
“…However, signals retrieved with the PPP approach could be contaminated by common mode error (CME), which may be present for multiple reasons (Dong et al, 2006). CME for time scale of days has been explored, but CME from high-rate GPS for a time scale of one hundred to one thousand seconds are little studied.…”
Section: Discussionmentioning
confidence: 99%